2013
DOI: 10.4269/ajtmh.12-0772
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Casa Segura: A Consumer Product Study of the Effect of Insecticide-Treated Curtains on Aedes aegypti and Dengue Virus Infections in the Home

Abstract: Abstract. The home, or domicile, is the principal environment for transmission of dengue virus (DENV) between humans and mosquito vectors. Community-wide distribution of insecticide-treated curtains (ITCs), mimicking vector control program-driven interventions, has shown promise to reduce DENV infections. We conducted a Casa Segura consumer product intervention study in Mérida, Mexico to determine the potential to reduce intradomicillary DENV transmission through ITC use in individual homes. Dengue virus infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 48 publications
(54 reference statements)
1
75
4
Order By: Relevance
“…aegypti females were described previously (Loroño-Pino et al 2013). Study homes distributed across ~30 neighborhoods (Colonias) in the southern and eastern parts of Mérida City were followed over a 15-month period from May 2009–July 2010.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti females were described previously (Loroño-Pino et al 2013). Study homes distributed across ~30 neighborhoods (Colonias) in the southern and eastern parts of Mérida City were followed over a 15-month period from May 2009–July 2010.…”
Section: Methodsmentioning
confidence: 99%
“…aegypti and intradomicillary DENV transmission (Loroño-Pino et al 2013), we performed monthly indoor collections of Ae. aegypti females (typically in >125 homes/month) and determined their DENV infection status.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti is ubiquitous in large urban centers and in smaller communities 2 and dengue is hyperendemic. 3,4 The mosquito is controlled through a combination of physical source reduction (removal or alteration of potential water-holding containers) and use of insecticides including the organophosphate temephos to eliminate larvae from water-holding containers and since 2000 pyrethroids have been used to control adults in and around homes. 5,6 Although insecticide pressure is high in large urban centers in Yucatan State, fine-scale refugia from insecticides are present.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti. 4,9 Another para mutation that is also strongly implicated in pyrethroid resistance involves a cysteine replacement (C1,534). 10,11 Our goal in this study is to test two alternative hypotheses concerning the evolution and spread of pyrethroid resistance in Yucatan State, Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…Mosquito-borne dengue is a major health problem in the Yucatán Peninsula of México (Loroño-Pino et al 1993, 2004, 2013; García-Rejón et al 2008). Several studies reported on the immature or adult stage of the primary local vector mosquito, Aedes ( Stegomyia ) aegypti (L.), for dengue virus.…”
Section: Introductionmentioning
confidence: 99%